2015
DOI: 10.1111/rda.12569
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Boar Sperm Cryopreservation: State of the Art and Current Perspectives

Abstract: ContentsWhile sperm cryopreservation is the best technology to store boar semen for long-term periods, only 1% of all artificial inseminations (AI) conducted worldwide are made using frozen-thawed boar sperm. With the emergence of long-term extenders for liquid storage, the use of cryopreserved sperm in routine AI is less required. However, banks of boar semen contain cryopreserved sperm and planning inseminations in AI centres may benefit from the use of frozen-thawed semen. Therefore, there is an interest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 128 publications
2
93
0
5
Order By: Relevance
“…The improvements made in cryopreservation methods for the past 15 years, including in composition of freezing and thawing extenders, and the knowledge that not all boars are "good sperm freezers" have shown that AI-doses cryopreserved today show good sperm quality and functionality at thawing [30]. Certainly, post-thaw sperm recovery rates over 70% in motility and viability are now usual, resulting in fertility outcomes near to those achieved with liquid-stored semen.…”
Section: Daily Use Of Frozen-thawed Semen and Of Sex-sorted Sperm In mentioning
confidence: 99%
See 1 more Smart Citation
“…The improvements made in cryopreservation methods for the past 15 years, including in composition of freezing and thawing extenders, and the knowledge that not all boars are "good sperm freezers" have shown that AI-doses cryopreserved today show good sperm quality and functionality at thawing [30]. Certainly, post-thaw sperm recovery rates over 70% in motility and viability are now usual, resulting in fertility outcomes near to those achieved with liquid-stored semen.…”
Section: Daily Use Of Frozen-thawed Semen and Of Sex-sorted Sperm In mentioning
confidence: 99%
“…New extenders for extending lifespan of FT-sperm and for cryopreserving sexed sperm are imperative [30,47].…”
Section: Seminal Plasma a Mine To Fully Discovermentioning
confidence: 99%
“…Moreover, selection of animals with good semen freezability for cryopreservation and AI is a crucial step to improve the fertility levels of frozen-thawed semen [9,10]. Furthermore, in some animal species, despite satisfactory results of fertility in liquid-stored semen, frozen-thawed semen does not give acceptable fertility results in AI practice in the commercial industry [2,3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Cryopreservation of semen allows the preservation of good genetic resources and the protection of endangered species [1][2][3][4][5]. While a great deal of eforts has been done over the last several years to improve the semen cryopreservation technology, efective cryosurvival of spermatozoa from various animal species, including the boar and stallion, still remains elusive and a cryobiological enigma [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation